Peculiarities of developing psychological resilience in law enforcement officers under martial law - Chuprynskyi, B. O.; Grachuk, V. S.; Karpinska, N. V. (Аналітично-порівняльне правознавство, 2025)
The article analyzes the peculiarities of developing psychological resilience in law enforcement officers under martial law. The aim of the article is to conduct a comprehensive analysis of psychological resilience in law enforcement personnel operating under martial law, covering its theoretical foundations, practical mechanisms of development, and the post-crisis support system. The study employed general scientific methods of cognition: analysis, synthesis, comparison, generalization, a systemic approach, and modeling. The research findings show that psychological resilience in law enforcement officers under martial law is formed as a dynamic construct that integrates neurophysiological, cognitive, and sociocultural factors. The study demonstrates that the polyvagal theory helps to understand evolutionarily conditioned response patterns, while modern cognitive paradigms emphasize the importance of self- regulation as a key prerequisite for effective stress management. It is concluded that resilience is not a fixed personality trait but develops through the interaction of biological potential with individually shaped value orientations and coping strategies that jointly define the boundaries of an officer’s psychological stability zone. On a practical level, the study shows that psychological resilience can be enhanced through systematic training that simulates combat situations in combination with rapid self-regulation techniques. It has been proven that developing neuromuscular memory, reducing decision-making latency, and maintaining coordinated teamwork help reduce the risk of professional errors. The research identifies that a multi-level system of psychological monitoring (screenings, debriefings) contributes to the creation of a sustainable culture of psychological safety within law enforcement agencies. The practical value of the study lies in the development of an effective integrated model for strengthening the psychological resilience of law enforcement personnel to ensure their readiness to act in wartime and crisis situations.